Fusion of OSS/BSS and ITSM Systems in ICT Industry - Yashi Wang; Lijuan Min; Yan Zhou (Dianxin kexue)
As fusion and openness become the trend of ICT industry,an OSS/BSS/ITSM system in a service provider or network operator needs effective integration with external systems and resources as well as among the internal isolated components,to provide better support to the operation.The characteristics of the operation of service providers and network operators were summarized,then,the requirements of the OSS/BSS components integration were analyzed,the integration tasks and the noticeable implementation issues were described,the typical misunderstandings in the ITSM and OSS/BSS fusion were pointed out,and the proper fusion approach and available system architectures were given.